Avaliação de efeito do Triclosan em órgãos internos de operárias campeiras de Bombus atratus (Hymenoptera: Apidae) - Provase, Michele (Universidade Federal de São Carlos, 2026)
Emerging contaminants (ECs) are synthetic or natural compounds that, despite their widespread use, present regulatory gaps regarding environmental threshold limits and potential ecotoxicological effects. Triclosan (TCS) has emerged as a compound of concern due to its persistence, high lipophilicity, and bioaccumulative properties. Although use restrictions have been imposed by regulatory agencies, the consumption of TCS-containing products increased during the COVID-19 pandemic, raising concerns about its environmental release. In this context, the present thesis was structured into three chapters. Chapter 1 comprises a scientometric and ecotoxicological analysis of the scientific literature addressing the effects of TCS on terrestrial organisms, focusing on bioaccumulation, oxidative stress, neurotoxicity, and reproductive effects in vertebrates and invertebrates. The findings reveal a substantial lack of studies involving insects, particularly pollinators, which limit comprehensive environmental risk assessments. Chapter 2 evaluated, for the first time, the effects of oral exposure to TCS in worker bees of Bombus atratus, using concentrations based on maximum limits permitted for continuous use in personal hygiene products as established by regulatory agencies. Histological and histochemical alterations were observed in the brain, including increased intercellular spaces and changes consistent with neurotoxic processes, which were associated with behavioral alterations detected through automated analysis using the EthoFlow software. Chapter 3 investigated the effects of TCS on the digestive system, with emphasis on the midgut, as well as on tissues comprising the hepato-nephrocytic system, including the fat body and pericardial cells associated with the dorsal vessel. Morphological and cellular alterations in these tissues indicated impairment of functions related to digestion, detoxification, and homeostasis. The effects observed in Chapters 2 and 3, even at sublethal levels, indicate potential functional impairment at the individual level, with possible implications for colony performance and maintenance. Overall, the results reinforce the need to establish specific guidelines for TCS residues in the environment and expand current knowledge on the impacts of this emerging contaminant on pollinators, particularly species of the genus Bombus.
Evaluation of the effects of triclosan on the internal organs of forager workers of Bombus atratus (Hymenoptera: Apidae)
Keywords: Contaminantes Emergentes; Ecotoxicologia; Neurotoxicidade; Efeito subletal; Abelhas; Emerging Contaminants; Ecotoxicology; Neurotoxicity; Sublethal Effects; Bumblebees; CIENCIAS BIOLOGICAS::MORFOLOGIA::CITOLOGIA E BIOLOGIA CELULAR; 15. Vida Terrestre